Answer:
-2
Step-by-step explanation:
Answer:
<u>66.22 </u>times 10=662.2
<u>4.03 </u>times 100=403
<u>0.108 </u>times 1000=108
Step-by-step explanation:
662.2 ÷ 10
403 ÷ 100
108 ÷ 1000
Answer:
-6s-c+1
Step-by-step explanation:
(-3s-4c+1)+(-3s+3c)
We have been given the above expression. To find the sum, we simply collect the like terms and combine them;
(-3s-4c+1)+(-3s+3c) = -3s + -3s -4c + 3c + 1
-3s + -3s -4c + 3c + 1 = -3s - 3s + 3c - 4c + 1
-3s - 3s + 3c - 4c + 1 = -6s - c + 1
Therefore;
(-3s-4c+1)+(-3s+3c) = -6s-c+1
Answer:
A
Step-by-step explanation:
T=D/R
You must isolate T so you divide R on both sides. This isolates T and gives you the answer.